(untitled) (CIPEEX, 2025)
The aim of this study was to describe, explore and highlight the role of phagocytosis in the innate immune response. Phagocytosis is essential for the immune system, being a mechanism for ingesting particles, pathogens and damaged cells from specialized cells called phagocytes. The main phagocytes include neutrophils, macrophages, and dendritic cells, which detect the target, for example a bacterium or a cell fragment. They have the Pattern Recognition Receptors or PRR that recognize Pathogen-Associated Molecular Patterns (PAMPs) or Damage Patterns (DAMPs) present in the offending agent. Then, binding to the surface of the pathogen occurs, resulting in adhesion, so the phagocyte promotes projections of the plasma membrane called pseudopods, which involve the offending agent internalizing it into the cytoplasm. The vesicle generated is known as the phagosome. The phagosome connects with lysosomes that have digestive enzymes and antimicrobial chemicals, forming the phagolysosome. Then, the target is degenerated by acid hydrolases and substances such as nitric oxide and reactive oxygen species overcoming the aggression. In addition, particles of the offending agent are presented on the surface of phagocytes through the Major Histocompatibility Complex or MHC. This presentation is essential for activating lymphocytes, the key cells of the adaptive immune response. Finally, phagocytosis helps maintain body homeostasis, as it removes dead cells and tissue fragments, corroborating the recovery of injuries and preventing the accumulation of waste that can lead to chronic inflammation, with the entire process being regulated by inflammatory signals and cytokines. In some diseases, phagocytosis can become dysfunctional. Thus, understanding this mechanism is essential not only for knowledge, but also for the development of new immunological therapeutic approaches. In summary, phagocytosis enables immune cells to recognize, swallow, and destroy pathogens, maintains physical balance, and cooperates in the adaptive immune response.